Investigation of Gas-Solid Flows in a Spout Fluidized Bed on Drag and Solid Stress: CFD-DEM, TFM, and Experimental Validation - Guo, Xinyao; Liu, Guodong; Zhao, Junnan; Wang, Runchun; He, Yurong (Journal of Chemical Engineering Research Updates, 2021)
In this work, experimental and numerical simulation methods are used to study the gas-solid two-phase flow in a three-dimensional rectangular spouted bed. In particular, the TFM and the CFD-DEM simulation results are compared with experimental data of the spouted bed. The influence of different drag models and friction stress models on the applicability of the simulation technology, Gidaspow, BVK, Koch-Hill, and Syamal-O’Brein drag models are investigated, respectively. Besides, the influence of the Syamal (S-R-O) and Srivastava-Sundaresan (S-S) friction stress models considering different transition points on the flow characteristics of particles in a spouted bed is also studied. Experimental verification shows that the Gidaspow drag, and S-S friction stress models are more consistent with experimental results. The fountain height predicted by CFD-DEM is closer to the experiment. It is found that the heterogeneous flow structure resulted in such a phenomenon in that the bubble cap blocked the gas flow pathway and increased the drag coefficient, while the bypass of the gas phase near the walls in the bubble reduced the drag coefficient.